TRANSFER OF BACTERIA-CONTAMINATED PARTICLES IN A KARST AQUIFER: EVOLUTION OF CONTAMINATED MATERIALS FROM A SINKHOLE TO A SPRING - Dussart-Baptista L.; Massei N.; Dupont J.P.; Jouenne T. (My University, 2003)
The transport of particle-associated bacteria during rain events in karst waters has been investigated. In this aim, we studied the correlations between water turbidity and enumerations of sessile (attached) and planktonic (non-attached) bacteria. We monitored physicochemical, i.e. turbidity, electrical conductivity, size and nature of the transported particles, and bacteriological properties of waters since their infiltration on a karst plateau to their discharge at a karstic spring. Results showed a decrease of the concentration of sessile bacteria at the sinkhole for high turbidities. This phenomenon might be explained by the arrival of lower contaminated material. On the other hand, the amount of sessile bacteria at the spring was not influenced by the turbidity values. These data demonstrated that slightly contaminated larger particles were not recovered, whereas small-size particles, which exhibited a higher bacterial contamination, were directly transferred (i.e. not affected by intra-karstic deposition) through the aquifer. Our study highlighted some significant differences between the bacteriological time series at the sinkhole and at the spring, which characterizes the storage/resuspension function of the considered karst system. Moreover, we show a decrease of the concentration of planktonic bacteria after transport through the system whereas no reduction of the sessile population occurred. The present data confirm that turbidity does not constitute a good indicator for bacterial contamination: if high turbidity corresponds to high bacterial contamination, low turbidity does not systematically exclude a risk of contamination by sessile organisms.
Keywords: GEOLOGIC INTERFACE; KARST; TURBIDITY; PARTICLE TRANSPORT; BACTERIA; BIOFILMS